Die sosiale konstruksie-model en die spanning tussen hoor en doen as reaksie op die prediking: Social construction model and the tension between listening and doing as reaction to preaching - Kleynhans, DJB; Kellerman, JS (Acta Theologica, 2000)
Preaching is the occurrence of communication through which the gospel of Jesus Christ is made known to the world, in order to change people’s lives. According to the social construction model each individual has an own constructed life story. This constructed life story acquires power over the individual, to such an extent that change cannot take place without deconstructing the life story. Deconstructing the life story or self-narrative leads to change. Thus the life story prevents th change that the preaching of the gospel wants to bring about. Deconstruction is furthered through communication. Preaching the gospel must be utilised to lead the individual to communication with self and others. When preacing the gospel it is more important to ask the right questions, than giving the right answers. The right questions will stimulate the hearer to tell his/her own story. In doing so, his/her life story will be deconstructed and changed according to the preached workd will take place.